Behavioural variation and learning across the lifespan in wild white-faced capuchin monkeys. (20th July 2020) - Perry, Susan
Abstract : Natural selection has evidently mediated many species characteristics relevant to the evolution of learning, including longevity, length of the juvenile period, social organization, timing of cognitive and motor development, and age-related shifts in behavioural propensities such as activity level, flexibility in problem-solving and motivation to seek new information. Longitudinal studies of wild populations can document such changes in behavioural propensities, providing critical information about the contexts in which learning strategies develop, in environments similar to those in which learning strategies evolved. The Lomas Barbudal Monkey Project provides developmental data for the white-faced capuchin, Cebus capucinus, a species that has converged with humans regarding many life-history and behavioural characteristics. In this dataset, focused primarily on learned aspects of foraging behaviour, younger capuchins are more active overall, more curious and opportunistic, and more prone to inventing new investigative and foraging-related behaviours. Younger individuals more often seek social information by watching other foragers (especially older foragers). Younger individuals are more creative, playful and inventive, and less neophobic, exhibiting a wider range of behaviours when engaged in extractive foraging. Whereas adults more often stick with old solutions, younger individuals often incorporate recently acquired experience (both social and asocial) when foraging. This article is part of the theme issue 'Life history and learning: how childhood, caregiving and old age shape cognition and culture in humans and other animals'.